PENGEMBANGAN MULTIMEDIA DALAM PEMBELAJARAN IPA MENGENAI MATERI CIRI MAHLUK HIDUP PADA TEMA 1 SUBTEMA 1 DI KELAS 3 SD - Katrin, Fransiska; Rozaqiyah, Honifah; Elvadola, Connyta (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2019)
The purpose of this research is to develop multimedia products as an alternative media in learning in elementary schools. This research is motivated by students who are less enthusiastic in learning which causes students to be inactive in the learning process in the classroom, which sometimes can happen due to external and internal factors. So that in this case the teacher is required to design appropriate learning facilities in order to make students more attractive and understand what the teacher says. This research is a research and development or Research and Development (R&D). Borg and Gall. The result of this research is a learning video for grade 3 SD Theme 1 Sub-theme 1 regarding the material characteristics of living things. Based on the results of this study, it can be concluded that it is important for teachers to have technological literacy to develop multimedia as a learning support so that students are able to understand the material properly and correctly so that they can improve the results of students' cognitive and apply them in everyday life. The suggestion from this research is that the product produced must go through validation and trial before it is used or applied to students.